THE FEASIBILITY ANALYSIS OF HANJELI FARMING (CASE STUDY: WALURAN MANDIRI VILLAGE, SUKABUMI DISTRICT, WEST JAVA) - Sahaya Aulia Azzahra; Nabila Nur Septiani; Lailatun Nikmah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The development of alternative staple foods is a solution to achieve food security and overcome dependence on rice imports. One of the local plants that has the potential to support food diversification programs is hanjeli (Coix lacryma-Jobi. L). On the other hand, hanjeli cultivation is almost extinct due to the conversion of agricultural land. The purpose of this study was to analyze the feasibility of hanjeli farming as an alternative food to support food security and to develop strategies for developing hanjeli farming to increase the profits of hanjeli farming. The data used is primary data through interviews with eight key figures. In addition, secondary data was obtained through literature study with the keywords "hanjeli", "agriculture", "agrotourism", "tourism village", and so on. The data analysis method used the R/C ratio to identify the feasibility of hanjeli farming. The results showed that hanjeli farming was feasible with an R/C ratio of 1.59, but efforts were still needed to increase the profits of hanjeli farming. The strategy to increase profits in hanjeli farming is the need to apply technology in hanjeli farming, improve the quality of human resources, add value to hanjeli products, and develop hanjeli agro-tourism sites.